Accounting Choices for Tangible Assets: A Study of Greek Firms - Apostolos Ballas; Vaia Panagiotou; Christos Tzovas (SPOUDAI - Journal of Economics and Business, 2014)
The purpose of this paper is to investigate the choices of Greek firms regarding the measurement of an item of a fixed tangible asset subsequent to its initial recognition, including impairment recognition, under IAS 16 and IAS 36 using a sample of Greek firms for the years 2005, 2007 and 2009. Results indicate that the cost model is more likely to be adopted by the more leveraged firms. In addition, it has been examined the compliance of the sample firms with disclosure requirements of IAS 16 and IAS 36. It appears that the disclosure compliance of the sample firms with the disclosure requirements of IAS 16 and 36 is influenced by firm's choice of valuation method for the measurement of an item of a fixed tangible asset subsequent to its initial recognition. It appears that the firms that adopt the revaluation method exhibit lower compliance rates.
Keywords: M41; 650; IFRS implementation; Fixed tangible assets; Greece